An ergonomic assessment of factors that contribute to work-related musculoskeletal disorders in hospital kitchens - Calayag, Chiqui Rosanna T. (College of Engineering, University of the Philippines Diliman, 2014)
This study focuses on the ergonomic assessment of hospital kitchen work to determine the presence of work-related musculoskeletal disorders (WMSD), their symptoms and their correlation to various individual attributes and work-related risk factors. Information on individual attributes, work design and psychosocial issues were obtained through survey along with the different symptoms of WMSD based on body part, frequency and intensity. The Rapid Entire Body Assessment (REBA), an ergonomic assessment tool, was used to determine the data on posture, repetition, force and load in terms of the kitchen employees. Correlation analysis was used to initially come up with a set of correlated variables. Stepwise regression was applied to determine a useful subset of predictors for the symptoms of WMSD and to address the presence of multicollinearity among the variables. Logistic regression was also used to model a relationship between the predictors and the presence of WMSD symptoms. The individual attributes that were determined to be predictors of symptoms of WMSD are weekly alcohol consumption, taking of medication for other illnesses, gender and surgical procedure undergone. Work-related risk factors that were determined to be predictors are work demand, control over work, cooking tasks, working hours per day, meal break utilization in minutes, frequency of meal break utilization and relationship with other employees.